2020
DOI: 10.7816/nesne-08-18-14
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Psychological Effects: A Review in Clinical Psychology Perspective

Abstract: The purpose of this review study is to examine the psychological effects of the COVID-19 outbreak on individuals in different groups. When the literature is examined, it can be stated that this epidemic causes negative emotional reactions such as anxiety, fear, and anger in adults, increases stress levels, increases their susceptibility to psychological disorders such as anxiety disorders, depressive disorders, posttraumatic stress disorder, and causes suicidal thoughts and insomnia. It can be stated that fear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…With the increased numbers of reported cases and deaths, COVID-19 studies have gained increasing attention from researchers in Turkey, as elsewhere. Studies conducted during COVID-19 in Turkey have focused on various types of topics, including scale adaptation (e.g., Atak & Yalcinkaya-Alkar, 2022;Ay et al, 2022;Karaköse & Akçinar, 2021a), psychological resilience (e.g., Bilge & Bilge, 2020;Kocakaya & Harmancı, 2022), preventive health behaviors (Alper et al, 2021;Karaköse & Akçinar, 2021b), and psychological well-being (e.g., Bekaroğlu & Yılmaz, 2020;Yıldırım & Güler, 2022). A recent review has stated that it is important to investigate how people with mental illnesses are affected by the pandemic as a result of increases in health anxiety and fear of infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the increased numbers of reported cases and deaths, COVID-19 studies have gained increasing attention from researchers in Turkey, as elsewhere. Studies conducted during COVID-19 in Turkey have focused on various types of topics, including scale adaptation (e.g., Atak & Yalcinkaya-Alkar, 2022;Ay et al, 2022;Karaköse & Akçinar, 2021a), psychological resilience (e.g., Bilge & Bilge, 2020;Kocakaya & Harmancı, 2022), preventive health behaviors (Alper et al, 2021;Karaköse & Akçinar, 2021b), and psychological well-being (e.g., Bekaroğlu & Yılmaz, 2020;Yıldırım & Güler, 2022). A recent review has stated that it is important to investigate how people with mental illnesses are affected by the pandemic as a result of increases in health anxiety and fear of infection.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review has stated that it is important to investigate how people with mental illnesses are affected by the pandemic as a result of increases in health anxiety and fear of infection. Thus, it is suggested to conduct screening studies for preventing recurrence or increase in the severity of psychological symptoms during the pandemic (Bekaroğlu & Yılmaz (2020). However, to the author's knowledge, there is no single study in Turkey examining the association between health anxiety, coping strategies, and the current mental health status using people diagnosed with mental illnesses.…”
Section: Introductionmentioning
confidence: 99%
“…It was stated that the sudden change in life due to the pandemic and the measures taken alongside the pandemic caused the individuals and societies to have psychological problems such as fear, worry, and stress (2,3). The feeling of fear experienced due to the pandemic had moderate and severe psychological effects on people (4)(5)(6)(7). The feeling of fear that emerges as a response to a real or perceived threat is one of the most prevalent consequences of the COVID-19 pandemic (8).…”
mentioning
confidence: 99%
“…To control the spread of the pandemic, the distance education model was implemented instead of face-to-face instruction in Turkey as of 23 March 2020 (10). In this process, university students are faced with certain restrictions related to the change in their daily lives, distance education, academic delays, and social life (4,11). In the relevant literature, it was identified that the university students felt fear, intolerance for uncertainty (12,13), stress (14) anxiety (11), and loneliness (15) in association with the COVID-19 pandemic.…”
mentioning
confidence: 99%